USM TENETS OF VALUES (RUKUN NILAI USM) TO FORTIFY THE APEX AGENDA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, January 2015 Universiti Sains Malaysia (USM) has established the 5 Tenets of Values (Rukun Nilai) in realising the concepts and philosophies behind I Love USM (Saya Sayang USM) and USM the Beloved Tower of Knowledge (USM Menara Ilmu Tercinta), with the hope of enriching the soul and character of its community in the effort to drive excellence (USMAPEX) and to provide the guidance towards achieving excellence.